A comparison of hominin teeth from Lincoln Cave, Sterkfontein L/63, and the Dinaledi Chamber, South Africa - Juliet K. Brophy (South African Journal of Science, 2019)
Prior to the recovery of Homo naledi from the Dinaledi Chamber of the Rising Star Cave system, the Middle Pleistocene fossil record in Africa was particularly sparse. With the large sample size now available from Dinaledi, the opportunity exists to reassess taxonomically ambiguous teeth unearthed at the nearby site of Sterkfontein. Teeth recovered from Lincoln Cave South and area L/63 at Sterkfontein have been considered ‘most probably Homo ergaster’ and ‘perhaps Archaic Homo sapiens’, respectively. Given the similarities shared between Lincoln Cave, area L/63, and the Dinaledi Chamber with regard to climatic/geologic depositional context and age, two teeth from the former sites, StW 592 and StW 585 respectively, were compared with corresponding tooth types of H. naledi from the Dinaledi Chamber. The results of our study indicate that the Lincoln Cave and area L/63 teeth are morphologically inconsistent with the variation recognised in the H. naledi teeth.